Enantioselective Synthesis and X‐ray Structure of (+)((4aS, 5S, 8aS)‐5, 8a‐Dimethyl‐7‐methyleneoctahydro‐2H‐spiro[naphthalene‐1, 2′‐[1, 3]dioxolan]‐5‐yl)methyl‐4‐iodobenzoate. Issue 7 (29th January 2019) - Leonelli, Francesca; Trombetta, Andrea; La Bella, Angela; Lucarelli, Giulio; Demitri, Nicola; Lamba, Doriano; Migneco, Luisa Maria; Marini Bettolo, Rinaldo
Abstract : Thed andl amino acid mediated enantioselective intramolecular aldol reaction of 4‐((1‐methyl‐2, 6‐dioxo‐cyclohexyl)methyl)‐pent‐4‐enal1 leading, after dehydration, to (‐)‐( R ) and (+)‐( S ) 4a‐methyl‐3‐methylene‐5‐oxo‐2, 3, 4, 4a, 5, 6, 7, 8‐octahydro‐naphthalene‐1‐carbaldehyde2 was explored. It was found that (‐)‐( R ) carbaldehyde2 is enantioselectively formed in the presence ofl ‐amino acids while (+)‐( S ) carbaldehyde2 is enantioselectively formed in the presence ofd ‐amino acids. (‐)‐( R ) Carbaldehyde2 was then transformed into ( + )‐22 . The absolute configuration and relative stereochemistry of the latter was established by single‐crystal X‐ray diffraction analysis of p ‐iodobenzoate ( + )‐23 . Abstract : Thed andl amino acid mediated enantioselective intramolecular aldol reaction of1 leading, after dehydration, to (‐)‐( R ) and (+)‐( S )2 was explored. It was found that (‐)‐( R ) carbaldehyde2 is enantioselectively formed in the presence ofl ‐amino acids while (+)‐( S ) carbaldehyde2 is enantioselectively formed in the presence ofd ‐amino acids.